2013
DOI: 10.2308/accr-50577
|View full text |Cite
|
Sign up to set email alerts
|

The Unintended Effect of Corporate Social Responsibility Performance on Investors' Estimates of Fundamental Value

Abstract: We provide theory and experimental evidence consistent with an unintended, causal relation between Corporate Social Responsibility (CSR) performance and investors' estimates of fundamental value that can be attenuated by investors' explicit assessment of CSR performance. Consistent with “affect-as-information” theory from psychology, we find that investors who are exposed to, but do not explicitly assess, CSR performance derive higher fundamental value estimates in response to positive CSR performance, and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
267
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(301 citation statements)
references
References 31 publications
23
267
1
10
Order By: Relevance
“…In 2011, approximately $3.74 trillion of the $25 trillion of investment assets in the United States was financed via socially responsible activities-a 22% increase since 2009 (Elliot, Jackson, & Peecher, 2014). The general business problem was that business leaders may lack adequate knowledge to understand the implications of CSR on the financial performance of their businesses (Wang et al, 2016).…”
Section: Problem and Purpose Of The Studymentioning
confidence: 99%
“…In 2011, approximately $3.74 trillion of the $25 trillion of investment assets in the United States was financed via socially responsible activities-a 22% increase since 2009 (Elliot, Jackson, & Peecher, 2014). The general business problem was that business leaders may lack adequate knowledge to understand the implications of CSR on the financial performance of their businesses (Wang et al, 2016).…”
Section: Problem and Purpose Of The Studymentioning
confidence: 99%
“…Empirical evidence ISSN 2157-6068 2015 provides support to the argument that CSR enhances financial performance in various terms. Two recent studies by Kim and Kim (2014) and Elliott et al (2014), indicate that CSR improves firm stock market valuation and the assessment of investor's estimates (perception) of fundamental value. Put it differently, investors incorporate information of corporate CSR activities on their assessments of firm valuation since they believe that those activities enhance corporate value (are value relevant).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Barney (1991), Balabanis et al (1998) and Jones (1995) document that corporate relations with stakeholders based on honesty, mutual trust and cooperation have greater probability to lead to competitive advantages which in turn can lead to enhance financial performance. Several researchers have provided empirical evidence that CSR could be a source of competitive advantage (Porter and Kramer, 2006;Inoue and Lee, 2011) and that CSR activities positively affect various aspects of firm performance within various sectors of economic activity (industrial, financial firms, services firms, etc) like firm reputation (Brammer and Millington, 2005), consumer satisfaction (Luo and Bhattacharya, 2006), employee commitment (Peterson, 2004;Plewa and Quester, 2011), cost of capital (Cheng et al, 2006), improved profitability and stock market performance (Kim and Kim, 2014;Elliott et al, 2014;Hillman and Keim, 2001;McGuire et al, 1988;Nelling and Webb, 2009;Hamil and Morrow, 2011). Also a recent study by Mallin et al (2014) indicated that CSR activities in Islamic banks adhere to the stakeholder theory which suggests a positive association between CSR and financial performance.…”
Section: Business Management and Strategymentioning
confidence: 99%
“…There are, at least, three major central points on this measure: sustainability disclosures (Adams & Frost, 2008;Joseph & Taplin, 2011), social and environmental disclosures (Tilt, 1994;Adams, Coutts, & Harte, 1995;Hackston & Milne, 1996;Patten, 2002;AlTuwaijri, Christensen, & Hughes, 2004;Cho & Patten, 2007;Clarkson, Li, Richardson, & Vasvari, 2008;Lu & Abeysekera, 2014) and corporate social responsibility (Roberts, 1992;Mahoney & Roberts, 2007;Delmas & Blass, 2010;Bouten, Everaert, Liedekerke, Moor, & Christiaens, 2011;Mahoney, Thorne, Cecil, & LaGore, 2013;Elliott, Jackson, Peecher, & White, 2014).…”
Section: International Researchmentioning
confidence: 99%
“…In other studies, corporate social responsibility relates to financial numbers (Roberts, 1992). Mahoney and Roberts (2007), Mahoney Thorne, Cecil and LaGore (2013), and Elliott et al (2014) assess the CSR performance by a previous index.…”
Section: International Researchmentioning
confidence: 99%